Revitalizing the United Nations Forum on Forests: critical issues and ways forward - Capistrano, D.; Kanninen, M.; Guariguata, Manuel R.; Barr, C.; Sunderland, Terry C.H.; Raitzer, David A. (Center for International Forestry Research, 2007)
CIFOR’s Forests and Governance Programme examines how decisions about forests and forestdependent people are made and implemented in order to promote the participation and empowerment of disadvantaged groups; the accountability and transparency of decision-makers and more powerful groups; and democratic, inclusive processes that support fair representation and decision making among all groups.